Development of food lists as a first step to develop a food frequency questionnaire for toddlers in a multi‐ethnic population. Issue 1 (10th October 2016) - Mubarik, Farya; Bhaskaran, Kalpana; Kho, Stephanie; Vereijken, Carel; Nambiar, Smita; Eussen, Simone; Muhardi, Leilani
Abstract : Aim: Toddlerhood is an important stage of growth, thus understanding the food intake of children in this age group is important. In Singapore, there is currently no simple tool, such as Food Frequency Questionnaire (FFQ), to collect dietary information from this ethnically diverse age group. Generating an appropriate food list is a crucial step in the development of a FFQ and this step is not clearly documented in the literature. The purpose of this study is to generate food lists and portion sizes for toddlers from three major ethnic groups in Singapore and document the processes involved in this first stage. Methods: A total of 30 mothers (equal number of Malays, Indians and Chinese) of 11–24‐month‐old children completed three‐day food records and participated in the focus group discussion. The reported food items were then categorised into food groups. Results: The food lists varied by ethnic groups with the longest list obtained from Chinese toddlers. There were also other foods that were then classified as common foods for all ethnicities. Commonly used utensils among the three ethnic groups were small‐sized bowls, plates, cups and spoons. For portion sizes, these utensils were typically half‐filled for the toddlers. Conclusions: As all Singaporeans have access to the same foods, the ethnic‐specific food lists generated in this study could be combined into one list. Together with portion sizes, this information can be used for developing a semi‐quantitative FFQ.